MONETARY POLICY OF THE BANK OF RUSSIA IN THE PERIOD OF FINANCIAL CRISES (2008 AND 2014) AND DEVELOPMENT BANKS - T. R. Maklakova; S. S. Matveevskii (Вестник университета)
The monetary policy of the Bank of Russia during the financial crises (2008 and 2014) and the use of development banks for economic growth have been considered. The multiple regression model, which allowed to evaluate the influence of a number of factors on the quantitative characteristics of the Bank of Russia monetary policy on the selected time interval has been developed and used. It has been concluded, that in the current сonditions a reduction in the key rate of the Bank of Russia does not lead to an increase in lending to the real sector of the economy. The proposals to increase the volume of lending to the Russian economy in the conditions of implementation of the current monetary policy of the Bank of Russia have been prepared. The usefulness of expanding the application of development banks in Russia to accelerate economic growth has been substantiated.